Pengaruh Konsep Diri dan Kreativitas Siswa Terhadap Prestasi Belajar Siswa dengan Menerapkan Pendekatan Kontekstual Pada Materi Termokimia (Jurnal Inovasi Pendidikan Kimia, 2023)
The aims of this study were (1) to determine the effectiveness of the application of a contextual approach to the subject matter of thermochemistry onstudent achievement in the odd semester students of class XI Science at Warta-Bakti High School Kefamenanu. (2) Knowing whether or not there is a relations between, self-concept and student creativity onstudent achievement by applying a contextual approach, to the subject matter of thermochemistry in class XI IPA SMA Warta-Bakti Kefamenanu. (3) Determine whether there is an influence of self-concept and student creativity onstudent achievement on the subject matter of thermochemistry. The variables in this study consisted of two independent variables, namely self-concept and student creativity and the dependent variable, namely student achievement. The analytical method used in this research is descriptive analysis and statistical analysis. From the data analysis obtained: (1). completeness of affective learning outcomes of 87%, completeness of cognitive learning outcomes of 85.11%, completeness of psychomotor learning outcomes on average of 87.70% and completeness of learning outcomes as a whole is said to be complete with a percentage of 86.12 %. C. Students' self concept and creativity are said to be very good, with an average of 86.85% and 86.14%, respectively. (2) Based on the calculation obtained Rxy = 0.8, the large contribution of variable X to variable Y is 64% and Ttable = 3.59, because Tcount ≥ Ttable is 9.64 3.59 then Ha is accepted and, Ho is rejected, which means, there is a relations between self-concept and student creativity on student achievement by applying a contextual approach, (3) There is an influence of self-concept and student creativity on student achievement by applying a contextual approach where, Fcount ≥ Ftable, which is 15.11≥3.59 at dk = 2 and dk = 20 at a significant level of 5%, then Ho is rejected and Ha is accepted.Keywords: Self-Concept, Creativity, Student Achievement, Contextual Approach.